Der ṭarab der Sängersklavinnen Masālik al-abṣār fī mamālik al-amṣār von Ibn Faḍlallāh al-ʿUmarī (gest. 749/1349): Textkritische Edition des 10. Kapitels Ahl ʿilm al-mūsīqī mit kommentierter Übersetzung - Gökpinar, Yasemin (Bibliotheca Academica - Reihe Orientalistik, 2021)
In "Der ṭarab der Sängersklavinnen", Yasemin Gökpınar presents a text critical edition of the three known manuscripts of the 10th chapter of Ibn Faḍlallāh al-ʿUmarī's (died 749/1349) "Masālik al-abṣār fī mamālik al-amṣār". In this monograph, she provides an unprecedented commented German translation of this important source on female singer slaves and their song repertoire in the context of Muslim court culture from the Abbasids to the Mamluks.The scientific interests of Dr. phil. Yasemin Gökpinar, Ruhr-University Bochum, and Austrian Academy of Sciences, Vienna, include Arabic music theory and history of sciences, their Greek sources, Arabic manuscript culture, text edition, Arabic-Islamic music culture and literature.